Islamic perspectives on marketing and consumer behavior planning, implementation, and control - Rishi, Bikramjit 1978- (Hershey, PA Business Science Reference, an imprint of IGI Global, 2015)
"This book brings together the best practices for entry and expansion of global brands into Islamic countries and is an essential reference source for professionals looking to incorporate the laws and practices of Islam into the global presence of their company"-- Provided by publisher.
Includes bibliographical references (pages 334-376) and index.
Electronic reproduction.
Keywords: Consumer -- Research -- Islamic countries; Marketing -- Islamic countries; Consumer behavior -- Islamic countries; Electronic books